2015
DOI: 10.5604/20831862.1188611
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of aerobic and anaerobic parameters with 400 m front crawl swimming performance

Abstract: The aims of the present study were to investigate the relationship of aerobic and anaerobic parameters with 400 m performance, and establish which variable better explains long distance performance in swimming. Twenty-two swimmers (19.1±1.5 years, height 173.9±10.0 cm, body mass 71.2±10.2 kg; 76.6±5.3% of 400 m world record) underwent a lactate minimum test to determine lactate minimum speed (LMS) (i.e., aerobic capacity index). Moreover, the swimmers performed a 400 m maximal effort to determine mean speed (S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(26 citation statements)
references
References 25 publications
1
21
1
2
Order By: Relevance
“…Thus, it may be likely that these parameters influence the S400 and consequently performance. These possible relationships are scarce in the lit-erature for the 400-m front crawl, except for one study [34] that used a different method (excess post-exercise oxygen consumption) to estimate the anaerobic contribution to T400 performance. Positive correlations were found (r = 0.80 and r = 0.44) between anaerobic contribution and performance, with the result being similar to that obtained in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it may be likely that these parameters influence the S400 and consequently performance. These possible relationships are scarce in the lit-erature for the 400-m front crawl, except for one study [34] that used a different method (excess post-exercise oxygen consumption) to estimate the anaerobic contribution to T400 performance. Positive correlations were found (r = 0.80 and r = 0.44) between anaerobic contribution and performance, with the result being similar to that obtained in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Swimming performance depends on physiological (endurance capacity, and anaerobic fitness), technical, and morphological factors (Pelayo et al, 2007 ; Lätt et al, 2009 ; Kalva-Filho et al, 2015 ). In relation to physiological aspects, studies have demonstrated that both the aerobic and anaerobic metabolisms are important to swimming performance (Zamparo et al, 2000 ; Figueiredo et al, 2011 ; Kalva-Filho et al, 2015 ). Considering the large time volume expended during training to improve specific metabolisms, knowledge about energy balance in different performances is important for specific training prescription (Toussaint and Hollander, 1994 ).…”
Section: Introductionmentioning
confidence: 99%
“…VO 2 (log transformed) and recovery time are linearly adjusted and VO 2 relative to the effort is determined at the end of exercise (Campos et al, 2016 ). Although the majority of studies have used the backward extrapolation technique in the first 30 s of recovery—assessing peak oxygen consumption (VO 2PEAK ) (Kalva-Filho et al, 2015 ; Campos et al, 2016 )—the time of monitoring can be extended, allowing its use to determine EPOC FAST (i.e., AnAl) (Kalva-Filho et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In swimming, the contribution of the aerobic metabolism to a maximal effort of 400 m may range from 25 to 83% of total energy and can be influenced by maximal oxygen uptake, metabolic thresholds and peak speed performed 15,16 . Thus, the use of taurine supplementation may oppose the possible overproduction of reactive oxygen species (ROS).…”
Section: Introductionmentioning
confidence: 99%